Ctrl + alt + del. - GUIDRY, TRIONA (Writer (Madavor Media), 2016)
In this article, the author offers suggestion for handling and managing technical emergency by writers. Topics discussed include use of file backups and system backup to prevent technical emergency, use of Acronis True Image software, and benefit of using of recovery and maintenance utilities such as Sophos Antivirus software.